Validity and Reliability of Persian Version of Dynamic Gait Index in Older Men - Morteza Abdiani; Masoud Golpayegani; Dariush Khajavi (University of Social Welfare & Rehabilitation Sciences, 2014)
Objectives: The present study, was carried out in the form of a MA thesis and with the of the validity and reliability of "dynamic gaiting index (DGI)" in elderly men.  Methods & Materials: This causal-comparative research was conducted on 180 elderly subjects living in Arak (aged 60 and over). The subjects were selected randomly and criterion for their admission was confirmation of a G.P. The data were analyzed using Exploratory Factor Analysis, main component analysis with Varimax rotation tests, Spearman’s correlation coefficient, Cronbach’s Alpha, and U-Man-Withney.  Results: The results indicated that the Persian version of DGI among older adults consists of one factor. The specific value of the factor was 6.091 which predicted 76.133 percent of variance. Cronbach’s Alpha was calculated 0.953. Reliability between the measurers showed a significantly high correlation between the two collected data sets which were collected by two different researchers. The test-retest reliability was also high and significant.  Conclusion: The research results showed that Persian version of the DGI among old men was acceptable and in accordance with its English version therefore, it can be used in clinical and therapeutic settings to identify the elderly who are exposed to falling risk.